Acquisition of knowledge about the dual graduation model: Focus on discovering knowledge in text in a systematic review - Canto , Cleunisse Aparecida Rauen De Luca (Seven Editora, 2023)
Dual degree models promote cooperation between universities and businesses. They are models that combine a theoretical-practical phase of learning in higher education institutions with a practical phase developed within partner companies, focusing on the development of real problems. In addition to Germany, countries such as Austria, Denmark, Finland, France, Holland, and Switzerland are the ones with the highest number of dual programs implemented. In this sense, the objective of this study was to identify the basic knowledge about the dual graduation model, in the light of the German model, based on the text mining technique. The acquisition of knowledge was conducted in a corpus composed of 18 articles that dealt with higher education, arising from the systematic review, and which were in English. The results made it possible to correlate the terms obtained from the application of mining methods or tasks, through specific algorithms, with the findings in the literature. To conclude, all the indicators obtained from the systematic review and the most relevant terms indicated in the text mining were correlated, generating a representative flow of the elements of the dual graduation model. DOI:https://doi.org/10.56238/devopinterscie-258